2016
DOI: 10.1007/s00394-016-1158-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between diet-related inflammation, all-cause, all-cancer, and cardiovascular disease mortality, with special focus on prediabetics: findings from NHANES III

Abstract: A pro-inflammatory diet, as indicated by higher DII scores, is associated with an increased risk of all-cause, CVD, all-cancer, and digestive-tract cancer mortality among prediabetic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
86
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 51 publications
14
86
0
Order By: Relevance
“…In the same study, significant associations were also found between the DII score and all-cancer mortality (HR = 1.46; 95% CI: 1.10–1.96), digestive-tract cancer mortality (HR = 2.10; 95% CI: 1.15–3.84), and CVD mortality (HR = 1.46; 95% CI: 1.18, 1.81). Similar results were found in another analysis with participants from the NHANES III after stratifying by the diabetic status of participants [38]. In this case, the highest risk of all-cause mortality was found among participants with prediabetes (serum HbA1c between 5.7% and 6.4%), as it is shown in Table 3.…”
Section: Mortality and The DII Scoresupporting
confidence: 84%
See 1 more Smart Citation
“…In the same study, significant associations were also found between the DII score and all-cancer mortality (HR = 1.46; 95% CI: 1.10–1.96), digestive-tract cancer mortality (HR = 2.10; 95% CI: 1.15–3.84), and CVD mortality (HR = 1.46; 95% CI: 1.18, 1.81). Similar results were found in another analysis with participants from the NHANES III after stratifying by the diabetic status of participants [38]. In this case, the highest risk of all-cause mortality was found among participants with prediabetes (serum HbA1c between 5.7% and 6.4%), as it is shown in Table 3.…”
Section: Mortality and The DII Scoresupporting
confidence: 84%
“…Table 3 shows five studies studying the association between the DII score and all-cause mortality [37,38,39,40,41]. In all studies except one, a higher risk of all-cause death was found among those participants with the highest pro-inflammatory values of the DII score.…”
Section: Mortality and The DII Scorementioning
confidence: 99%
“…The food components of this dietary pattern such as preserved or processed foods, deep fried foods, meat and sugary drinks plausibly contribute to an increased risk of MetS. This dietary pattern was often accompanied by high intakes of total fat, saturated fat and simple sugar which may stimulate the production and secretion of certain pro-in ammatory cytokines including C-reactive protein (CRP) and further increase systemic in ammation [24,30,35]. The pro-in ammatory cytokine CRP has been known to be closely related to in ammation and MetS [36].…”
Section: Discussionmentioning
confidence: 99%
“…Further corroboration of the validation of the DII is that fact that it has been associated with a wide range of outcomes associated with inflammation. The DII was previously associated with several types of cancer (e.g., colorectal, prostate, pancreas, lung, esophageal) (612), cardiovascular disease (13), components of metabolic syndrome (5), telomere length (14), obesity (15), asthma (16), and mortality (17, 18). However, previous construct validation studies using inflammatory markers were mainly conducted among populations that were mainly European Americans.…”
Section: Introductionmentioning
confidence: 99%